EKSISTENSI `URF PADA PERUBAHAN QAWL AL-SYĀFI`Ī (TELA`AH TERHADAP HUKUM MUNĀKAHĀT) - Muhammad Harun (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
`Urf as one of the methods istinbāţ there is no law in the legal constructs formulated by al-Syāfi`ī the book of al-treatise. However, the phenomenon of change qawl al-Syāfi`ī of qawl qadim to Jadid not based on texts which have implications for the interpretation of the existence of two `Urf; `Urf effect or no effect on these changes. In the case of the existence of the field of `Urf Munākahāt apparently only affects the order tanfīz. While in the process of change qawl al-Syāfi`ī remains influential in the texts. So it is understandable, why not include the al-`Urf Syāfi`ī on istinbāţ methods besides legal interpretation that` Urf effect on qawl change must be understood in the context of tanfīz.ملخص: `العرف وأسلوب واحد للحكم غير موجودة في قانون البنى التي صاغها شافعي على قناة اطروحة. لكن ظاهرة تغير القول المفيد القول المفيد شافعي القديم إلى الجديد لا يقوم على ناش تورط اثنين من التفسيرات لوجود `العرف. `أثر العرف أو أي تأثير على هذه التغييرات. في حالة وجود مجال الزواج ويبدو أن تؤثر فقط على `العرف حفاظ على النظام بينما في عملية التغيير يبقى القول المفيد شافعي تأثيرا في ناش.